Imputations for missing data in income variables. Permanent Household Survey (EPH). Gran Buenos Aires, Argentina / 1990-2010 - Donza, Eduardo Ricardo (2016)
Fil: Donza, Eduardo Ricardo. Pontificia Universidad Católica Argentina. Observatorio de la Deuda Social Argentina; Argentina